The Importance of Peace and Stability for the Development of Sub-Saharan Africa - Kaczmarek, Filip (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2017)
This analysis of the situation of Sub-Saharan Africa states shows that it is impossible to achieve permanent, sustainable development in the conditions of war or other military conflicts. External aid for such countries is first and foremost humanitarian aid. Although such aid is necessary and helps save human lives, it does not eliminate the reasons for conflicts and is unable to ensure stable development. In the states with the worst situation, humanitarian aid does not have a significant influence on reducing migration trends. Before permanent development occurs, conflicts have to be efficiently resolved and their reasons eliminated or radically limited. The social and economic development of SSA states, which are currently suffering from armed conflicts and instability, is therefore primarily dependent on political rather than economic solutions.

Z analizy sytuacji państw Afryki Subsaharyjskiej wynika, że trwały, zrównoważony rozwój w warunkach wojny czy innych konfliktów zbrojnych nie jest możliwy. Pomoc z zewnątrz ma w tych krajach przede wszystkim charakter pomocy humanitarnej. Jest ona potrzebna i ratuje ludzkie życie. Sama w sobie nie likwiduje jednak przyczyn konfliktów ani nie jest w stanie zapewnić trwałego rozwoju. W przypadku państw o najgorszej sytuacji, pomoc humanitarna nie wpływa też w istotny sposób na zmniejszenie tendencji migracyjnych. Budowanie trwałego rozwoju musi być poprzedzone skutecznym zakończeniem konfliktów oraz wyeliminowaniem lub radykalnym ograniczeniem ich przyczyn. Rozwój społeczny i gospodarczy państw Afryki Subsaharyjskiej, doświadczających konfliktów zbrojnych i niestabilności jest zatem uzależniony w pierwszej kolejności od rozwiązań politycznych, a nie ekonomicznych
Znaczenie pokoju i stabilizacji dla rozwoju Afryki Subsaharyjskiej
Keywords: Sub-Saharan Africa; development, military conflicts; instability; Afryka Subsaharyjska; rozwój; konflikty zbrojne; niestabilność